2012
DOI: 10.1002/hep.25855
|View full text |Cite
|
Sign up to set email alerts
|

Patients transplanted for nonalcoholic steatohepatitis are at increased risk for postoperative cardiovascular events

Abstract: Nonalcoholic steatohepatitis (NASH) is an independent predictor of coronary artery disease (CAD). Our aim was to compare the incidence of cardiovascular (CV) events between patients transplanted for NASH and alcohol (ETOH)-induced cirrhosis. This is a retrospective cohort study (August 1993 to March 2010) of 242 patients (115 NASH and 127 ETOH) with 12 months follow-up after liver transplantation (LT). Those with hepatocellular carcinoma or coexisting liver diseases were excluded. Kaplan-Meier's and Cox's prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 51 publications
(86 reference statements)
7
160
2
4
Order By: Relevance
“…Furthermore, death because of a cardiovascular event and the frequency of a cardiovascular event were analyzed. 16 When we pooled the data from the 3 studies, which including ours and 2 other studies, 11,17 and compared NASH recipients versus alcoholic cirrhosis recipients, the probability of a cardiovascular event-related mortality remained similar between the groups (16 of 264 patients vs 7 of 275 patients; mean, 2.3; range, 0.7-8.2; P = .19).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, death because of a cardiovascular event and the frequency of a cardiovascular event were analyzed. 16 When we pooled the data from the 3 studies, which including ours and 2 other studies, 11,17 and compared NASH recipients versus alcoholic cirrhosis recipients, the probability of a cardiovascular event-related mortality remained similar between the groups (16 of 264 patients vs 7 of 275 patients; mean, 2.3; range, 0.7-8.2; P = .19).…”
Section: Discussionmentioning
confidence: 87%
“…The relatively smaller sample size in our study and the higher proportion of patients with a history of pretransplant cardiovascular disease among NASH transplants in the other reported study may partly explain the differences in findings. 11 In a recently meta-analysis of 9 studies on 4237 patients who received a liver transplant for various liver diseases (717 NASH), no differences in patient survival at 1, 3, and 5 years was shown when transplant patients with NASH and without NASH were compared. However, the authors concluded that NASH patients died more often from cardiovascular causes than the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation is the only option left for NASH patients with cirrhosis. However, even after transplantation there is risk of recurrence of disease and cardiovascular complications [99].…”
Section: Role Of Fxr Agonist In Nafld Treatmentmentioning
confidence: 99%
“…12 In addition, even the highly selected NASH patients currently being transplanted have a higher rate of cardiovascular events compared with patients transplanted for other indications. 13,14 This has resulted in some advocating for combined liver transplantation and gastric sleeve resection.…”
Section: Posttransplant Outcomes In Nash Patientsmentioning
confidence: 99%